2013
DOI: 10.1007/s10661-013-3131-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bridge construction on songbirds and small mammals at Blennerhassett Island, Ohio River, USA

Abstract: Construction of man-made objects such as roads and bridges may have impacts on wildlife depending on species or location. We investigated songbirds and small mammals along the Ohio River, WV, USA at a new bridge both before and after construction and at a bridge crossing that was present throughout the study. Comparisons were made at each site over three time periods (1985-1987 [Phase I] and 1998-2000 [Phase II] [pre-construction], 2007-2009 [Phase III] [post-construction]) and at three distances (0, 100, 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…However, forest loss associated with roads is only part of the story. Roads influence vegetative communities [57], fish and wildlife assemblages [58][59][60][61], soil chemistry [62], stream sedimentation [63], stream morphology [64], water quality [65], and benthic macroinvertebrates [63,65]. Khanal [54] found that southern parts suffer more shrinkage of forest cover than northern parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, forest loss associated with roads is only part of the story. Roads influence vegetative communities [57], fish and wildlife assemblages [58][59][60][61], soil chemistry [62], stream sedimentation [63], stream morphology [64], water quality [65], and benthic macroinvertebrates [63,65]. Khanal [54] found that southern parts suffer more shrinkage of forest cover than northern parts.…”
Section: Discussionmentioning
confidence: 99%
“…Mahananda et al [67] modeled three categories of forest (i.e., evergreen forest, semi-evergreen forest, and deciduous forest) based on the relation between the NDVI and plant species diversity. Around 2000, heavy road expansion resulted in a significant loss in forest cover [54], affecting the NDVI and likely biota [57,60,61,63] and environmental quality [62][63][64][65]. However, in 2022, because of the active involvement of local communities in forest conservation and protection, the NDVI improved.…”
Section: Discussionmentioning
confidence: 99%